The Role of Self-Contained Consumer Protection Services (LPKSM) in Providing Protection to Consumers on The Circulation of Hazardous Drugs - Ni Nyoman Muryatini; Lilis Yuningsih (Jurnal Hukum Prasada, 2024)
The acute kidney injury cases that occurred recently highlight the urgency of consumer protection issues in Indonesia. The Consumer Protection Law in Indonesia is a preventive effort by the government to provide legal certainty for consumers. LPKSM is mandated by the Consumer Protection Law to provide legal protection to consumers. This research aims to examine the extent of the role of LPKSM in providing protection to consumers. The research method used in this research is normative juridical research. The approach used is a statute approach and a legal concept analysis approach. The technique of collecting legal materials by conducting document studies related to the problems studied and also primary, secondary and tertiary legal materials, then interpreting and reviewing related laws and regulations. Based on the results of the research that has been conducted, consumer protection is an issue that should receive attention from all parties, including the government, society, and business actors. LPKSM is a non-profit institution that, undoubtedly, requires operational costs, which often become a hindering factor in fulfilling its mandate according to the Consumer Protection Law. The government's role is crucial in this regard, specifically in providing financial support to LPKSM to fulfill its duties effectively. In addition to monitoring the circulation of goods and/or services in the market, LPKSM also provides consumer education and has the authority to file lawsuits against businesses that harm consumers.